Hemoglobin Levels of Pregnant Women Consuming Multiple Micronutrients VS Fe+Folate in Banggai District - Lalusu, Erni Yusnita; Luwiati, Luwiati; Balebu, Dwi Wahyu; Otoluwa, Anang Samudera (Poltekkes Kemenkes Palu, 2023)
Providing Fe+Folate for a long time to pregnant women has not been able to show a significant reduction in the incidence of anemia during pregnancy. This study aims to determine the effect of consuming multiple micronutrient supplements on the Hb levels amonv pregnant women in Banggai District. This was a quasi-experimental study with a non-randomised community trial and pre and post-test control group design, which involved 48 pregnant women assigned in the intervention and control groups. This study was conducted in Banggai District in 2020. The intervention group involved pregnant women who were administered with Multiple Micronutrient (MMN) supplements based on the UNIMMAP formula. The control group involved pregnant women who were administered with Fe+Folate supplements. Supplements were administered during the second trimester of pregnancy. Hemoglobin levels were assessed at the 12th week and 24th week of pregnancy. Various anthropometric characteristics and measures were assessed at study baseline. Hemoglobin levels were assessed using the Hemocue Hb 201 tool. Nutritional intake was assessed using the Semi Quantitative-Food Frequency Questionnaire (SQ-FFQ). Data were analyzed using the chi-square test, independent t-test and dependent t-test. The results of the study showed that during the second trimester of pregnancy, the mean hemoglobin level in the intervention group who were given MMN decreased by 0.3 g/dl (p-Value=0.143) and in the control group who were given Fe+Folate decreased by 0.1 g/dl (p-Value=0.408). The adifference in the decrease was not statistically significant. At the 24th week of pregnancy, the mean hemoglobin level of pregnant women who were given MMN was 0.1 g/dl higher than those who were given Fe+Folate. Such difference was not statistically significant (p-Value=0.415). Further study needs to be conducted to examine the effect of MMN and Fe+Folate on hemoglobin levels based on anemia status, characteristics of pregnant women and health status.